Community Awareness And Understanding Of Waqf In Malaysia: Experience Of The States Islamic Religious Council - Farhana Mohamad Suhaimi; Ab Rahman, Asmak (Universiti Sains Islam Malaysia, 2024)
This study aims to identify the awareness and understanding of the Muslims in Malaysia regarding the development of waqf property. An understanding of the importance of waqf and its impact on the Muslims economy is significant as the community are the backbone supporting the charitable institutions survival. In fact, the lack of public awareness on the project will affect the development of waqf. The research conducted is in the form of field research implemented through interviews with the selected State Islamic Religious Council (MAIN) Waqf Section officers as MAIN had vast experience in leading the society on waqf property management. In addition, review of literature was performed as part of the study. The study focuses on the awareness and understanding of the Muslims in Malaysia on waqf property. The study found that Muslims awareness on the waqf property in Malaysia varies according to states. This is due to the different approaches by MAIN in developing the waqf property in their respective states. Overall, the Muslim community has awareness regarding the waqf propery, however, the understanding of the waqf property still needs to be improved. Efforts to increase awareness and understanding of the relevant endowment should be diversified with an effective approach to optimized endowment role in community development, particularly in Malaysia.